Cancer Awareness Campaign in Ghana (African Journal of Biomedical Research, 2023)
There is a wide variety of health conditions that are associated with high disease burden that require significant attention in the Ghanaian community. Of all these pressing issues, cancer stands out as the most rapidly advancing cause of morbidity and mortality. Cancer is the abnormal growth of cells that has the potential to invade adjacent structures and spread to distant sites especially if not detected and treated early. In this study,we discuss developmental tools that are needed to gain recognition of cancer, to create the necessary awareness and provide education for all community members by describing the disease,its signs, symptoms, treatment modalities as well as where to seek treatment. With such education, the Ghanaian populace would be more informed and the knowledge gained will influence the training and socialization of the target audience